Higher doses of cabergoline further improve metabolic parameters in patients with prolactinoma regardless of the degree of reduction in prolactin levels. (22nd April 2013) - Ciresi, Alessandro; Amato, Marco Calogero; Guarnotta, Valentina; Lo Castro, Flavia; Giordano, Carla
Summary: Objective: Currently available studies that fully analyse the metabolic parameters in patients with prolactinoma are scarce and discordant. The aim of this study was to evaluate the metabolic effects of cabergoline (CAB) treatment in patients with newly diagnosed prolactinoma in relation to disease control and CAB dosage. Design: This is a retrospective clinical‐based therapy analysis. Patients: Forty‐three patients with prolactinoma (eight men, 35 women), aged 33·65 ± 11·23 years, were evaluated metabolically at baseline and after 12 months of CAB treatment. Measurements: Body mass index (BMI), systolic and diastolic blood pressure, waist circumference (WC), lipid profile, haemoglobinA1c (HbA1c), glucose and insulin levels (and their areas under the curve, AUC) after an oral glucose tolerance test, homoeostasis model assessment of insulin resistance (Homa‐IR) index, insulin sensitivity index (ISI) Matsuda, oral disposition index (DIo) and visceral adiposity index (VAI) were measured at baseline and after 12 months of treatment. Results: Twelve months of CAB reduced WC ( P  < 0·001), total ( P  = 0·001) and low‐density lipoprotein \terol ( P  < 0·001), triglycerides ( P  = 0·024), fasting insulin ( P  < 0·001), AUCINSULIN ( P  < 0·001), HbA1c ( P  = 0·022), Homa‐IR ( P  < 0·001) and VAI ( P  < 0·001), with a concomitant increase in high‐density lipoprotein cholesterol ( P  < 0·001) and in ISI Matsuda ( P  < 0·001), regardless of the degree of reduction in prolactin levels. The patients receiving higher doses (>0·50 mg/week) of CAB showed lower BMI ( P  = 0·009), fasting insulin ( P  = 0·001), Homa‐IR ( P  < 0·001) and VAI ( P  = 0·018) and higher ISI Matsuda ( P  = 0·002) and DIo ( P  = 0·011), compared with those on lower doses. Conclusions: A significant metabolic improvement was observed in patients with prolactinoma after 12 months of CAB treatment, especially when higher doses were used, highlighting the importance of considering the metabolic profile in these patients and the role of active treatment with high CAB doses.